Mengenalkan Sains dan Teknologi untuk Siswa Usia Sekolah Dasar di Kawasan Pesisir Teluk Tomini Gorontalo - Lukman A.R Laliyo; Thayban Thayban; Haris Munandar; Erga Kurniawati; Citra Panigoro; Kostiawan Sukamto (Universitas Negeri Gorontalo, 2023)
This community service discusses the importance of introducing science and technology to students at primary school age. The age range of primary school students is between seven and twelve years old, where children's development is continuous. During this time, students begin to recognise new objects around them and explore the world with natural curiosity. Children's talents develop in various aspects, including religious and moral beliefs, physical-motor, cognitive, verbal, social-emotional, and artistic abilities. the sample in this community service is elementary school students of Molotabu Village. The survey results showed that as many as 78% of primary school students were able to identify the pictures that constitute science and technology, demonstrating their understanding of these basic concepts. Next, students are engaged in simple experiments using materials that are easily found around them. These experiments aim to give students hands-on experience in testing their hypotheses or ideas about how things work. In the simple experiment, about 60% of the students managed to carry it out well.